The Correlation Between Fatigue and Sleep Quality among Patients with Heart Failure - Ferdy Lainsamputty; Hsing-Mei Chen (NurseLine Journal, 2018)
Heart failure (HF) patients may experience fatigue and poor sleep quality due to impairment in cardiac structure or function. These distressing symptoms may create a vicious circle leading to poor outcomes but often undervalued and ignored among patients. This study aimed to investigate the relationship between fatigue and sleep quality among patients with HF in Indonesia. A cross-sectional, correlational study design was performed with 153 convenience samples recruited from a cardiology outpatient department at a medical center in Indonesia. Descriptive statistics, bivariate analyses (independent t-tests, one-way Analysis of Variance, and Pearson correlation), and hierarchical regression analysis were utilized to analyze the data. Instruments included demographic characteristics and clinical variables questionnaire, the Multidimensional Assessment of Fatigue (MAF), and the Pittsburgh Sleep Quality Index (PSQI). The mean age of participants was 61.86±10.79 years old and the mean duration of HF diagnosis was 4.26±5.48 years. All participants complained of fatigue, while 73.2% had poor sleep quality. Participants who were poor sleepers had a higher proportion of individuals used massage, not having taken dyslipidemia drugs, had normotension or well-controlled blood pressure, and suffered from hypertensive heart disease (HHD) and renal diseases. All fatigue domains, except the degree of interference in ADL, was significantly associated with sleep quality. However, only the timing domain determined sleep quality, meaning, the longer the fatigue, the poorer the sleep quality. This study suggests future interventions should be directed to decrease the level of severity, distress reduction, and particularly shorten fatigue duration should be developed to improve the sleep quality.